Realitas Kehidupan Islami dalam Novel Surat Kecil untuk Tuhan Karya Agnes Davonar (Kajian Mimetik) - Zulfatun Anisah (ISTAWA, 2018)
The value of Islamic education is occupied in everyday life, depicted also in literary works. One of them is the novel "Little Letter to God". The Islamic values contained in the novel reflect the values of life. On the social values depicted kinship attitudes interwoven between humans, mutual help-help, and mutual cooperation with each other. The value of education is also depicted according to the teachings of the Prophet Muhammad is seriously in search of knowledge until death to pick human. Moral education can also be used as a reference. Wise in dealing with any event or fate. Do not blame others when he / she gets the accident. Able to deal with various problems with a spacious heart. In addition, the value of religiosity in the novel SKUT reflects that in initiating any activity should be based on prayer, and sincere in receiving trials and destiny